As ferramentas da intolerância e seus efeitos: os cristãos novos e o julgo da inquisição portuguesa - Melo Filho, Reinaldo Peixoto de (2018)
In the perspective of Cultural and Social History, this dissertation proposes a pertinent study on the effects of the intolerant procedures that were implanted by the Holy Office of the Inquisition in the Iberian Peninsula and in its Colonies in the Modern Age, with the objective of analyzing the causal relations and in effect, established by the dominant over the dominated, that is, starting from the cause of this relationship, we identified the Inquisition and its tools, used as strategies for the implementation of power, revealed in the laws that govern procedures and in the procedures themselves, for example, the implementation of torture, as well as the officials who executed the service. Therefore, we investigate the consequences of this action, the effects in the religious, cultural and social aspect, for this, we seek to analyze from the forms of resistance to the action of the dominator, revealing a tactical attitude of the dominated in an attempt to guard against the procedures from the action of the Holy Office to the ultimate aspect of the dilution of identity that occurred during this process, a situation that will generate a social impact that extends to this day, since the question of the Jewish identity of the new Christians and their descendants reveals a problematic which propagates through the centuries and is not extinguished in the present, for each epoch presents its own claims of its historical context, revealed through the analysis of bibliographical material and other historical documents that will illuminate this relationship of belonging that seemed never to be completely extinguished .